Quality improvement initiative to improve pulmonary function in pediatric cystic fibrosis patients. Issue 11 (22nd August 2020) - Filbrun, Amy G.; Enochs, Catherine; Caverly, Lindsay; Rajala, Kelsey; Powell, Corey; Merrick, Emily; Nasr, Samya Z.
Abstract: Background: Our Cystic Fibrosis (CF) Center initiated a Quality Improvement (QI) project in November 2017 with the goal of improving our patients' forced expiratory volume in 1 second (FEV1) percent predicted (pp) and continued for 1 year. Our specific aim was to increase the relative mean FEV1 pp by 5% in 12 months for CF patients 6 to 21 years old with FEV1 ≤ 80 pp. Methods: We identified patients with FEV1 ≤ 80 pp, developed cause and effect diagrams (fishbones) to identify contributing factors to FEV1 ≤ 80 pp, and created flowcharts to address barriers. The barriers to adherence that may result in FEV1 ≤ 80 pp were studied using a fishbone. A standardized approach across providers was implemented to individualize care for each patient. Each discipline developed a flowchart to address barriers to improving FEV1. Results: Forty patients were identified (43% male). Their mean age was 16.8 years (range 8.2‐21.5 years). Mean FEV1 pp at baseline was 58.6 (range 30‐80). The fishbone identified needs for continuing education for patients/families, and providing a treatment plan at each clinic visit. After 6 months of implementation, patients had an improvement in mean FEV1 pp by 6.4% (CI, 0.4%‐12.9%). At 12 months, mean FEV1 pp had improved by 14% (CI, 6.5%‐21.4%), which exceeded our goal of 5%. Conclusion: Through this ongoing project, team members, patients, and families partnered to improve lung function in pediatric CF patients. Flowcharts facilitated a standardized approach across providers to develop individualized treatment plans for patients, which resulted in improved lung function.